2007
DOI: 10.1080/09513590701350341
|View full text |Cite
|
Sign up to set email alerts
|

Ovulation induction treatment and risk of borderline ovarian tumors

Abstract: Our series produced no evidence that ovulation induction treatment predisposes women to the development of borderline ovarian tumors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 14 publications
5
18
0
1
Order By: Relevance
“…We found elevated risk of borderline ovarian tumors in women treated with ART, in line with two previous studies (7, 45), but in contrast to a further three (41, 46, 47). In our study, we could not observe difference in risk among nulliparous and parous women.…”
Section: Discussionsupporting
confidence: 92%
“…We found elevated risk of borderline ovarian tumors in women treated with ART, in line with two previous studies (7, 45), but in contrast to a further three (41, 46, 47). In our study, we could not observe difference in risk among nulliparous and parous women.…”
Section: Discussionsupporting
confidence: 92%
“…The management of such patients has been a controversial task, particularly since the use of fertility drugs was identified as a risk factor for the development of ovarian neoplasms in some studies [7,8] ; however, other studies have not been able to confirm this association [9,10] . A meta-analysis of all the available literature found that infertility treatment did not independently increase the risk of ovarian neoplasm; however, infertility itself was an independent risk factor for this disorder [11] .…”
mentioning
confidence: 96%
“…Other studies have reported an increased risk of ovarian cancer in women treated with fertility drugs [15-17,21,22,42,44,46,49-51]. Finally some studies have reported an increased risk especially for borderline ovarian tumors [16,21,22,36,42,49,50]. …”
Section: Discussionmentioning
confidence: 99%